2017
DOI: 10.1111/inr.12405
|View full text |Cite
|
Sign up to set email alerts
|

Developing nursing research in the United Arab Emirates: a narrative review

Abstract: There are specific challenges for the United Arab Emirates. However, the country is well placed to learn from the experiences of colleagues elsewhere. Time and commitment is required to build the solid foundations necessary to ensure robust, sustained growth. Identifying research capacity as both a process and outcome at the outset may also assist. Further, it may be prudent to consider initiating a Gulf Coast Countries' collaborative approach to building research capacity to harness scare resources and create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…According to Gray [30] and Smith [1], the quality of published outcome analysis definitions and the registration of randomized controlled trials are not often optimal in nursing journals. Unnecessary delays in beginning a research project may occur because of organizational and/or personnel factors, such as time pressure or limited knowledge; lack of time and knowledge are important barriers to research [3,31]. From a policy and professional perspective, nurses and other allied health practitioners should contribute to research to develop strong research basis for improving patient care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Gray [30] and Smith [1], the quality of published outcome analysis definitions and the registration of randomized controlled trials are not often optimal in nursing journals. Unnecessary delays in beginning a research project may occur because of organizational and/or personnel factors, such as time pressure or limited knowledge; lack of time and knowledge are important barriers to research [3,31]. From a policy and professional perspective, nurses and other allied health practitioners should contribute to research to develop strong research basis for improving patient care.…”
Section: Discussionmentioning
confidence: 99%
“…From a policy and professional perspective, nurses and other allied health practitioners should contribute to research to develop strong research basis for improving patient care. Moreover, nursing is still struggling to develop as an academic discipline, in addition to becoming a significant contributor to collaborative research [31]. Nurses have highlighted the importance of nursing research and acknowledge that they are connected to professional development and advanced clinical nursing care and are essential to recognize that improving nurses’ research ability is an outcome in itself [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature presented here builds on a previous study (McCreaddie et al, 2018) that reviewed the building of nursing research capacity and standards for the UAE. The authors of that study conducted a literature search of nursing research in UAE and globally, which initially yielded 332 hits, then was reduced to 60 after screening.…”
mentioning
confidence: 99%
“…Because healthcare research activity in the UAE, especially among nurses, is still in its infancy [35], the study team agreed to select the highest-ranked research priorities to focus on as a starting point. Therefore, in regard to the consensus cut-off points, the group agreed that the criterion used to determine consensus that a research priority was of high importance was that the identified priority was rated as important/very important by at least 90% of participants.…”
Section: Methodsmentioning
confidence: 99%